2023
DOI: 10.1186/s13102-023-00666-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of back school-based intervention on non-specific neck pain in adults: a randomized controlled trial

Abstract: Background Neck pain has a high prevalence and socioeconomic impact worldwide. The Back School consists of programs that include exercises and educational interventions to treat back pain. Accordingly, the main objective was to evaluate the effects of an intervention based on Back School on non-specific neck pain in an adult population. The secondary objectives were to analyze the effects on disability, quality of life and kinesiophobia. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Although, improvement was greater in the combined KT and CSE group, showing that modalities such as KT and CSE are effective in the treatment of NSCLBP. Additionally, a study by Hernandez-Lucas et al (2023) evaluating the effects of the Back School on non-specific neck pain in adults aged ≥18, showed a beneficial effect on kinesiophobia, however, this study did not have a post-intervention follow-up, making it difficult to ascertain its long-term effect. Furthermore, due to the small sample size, generalisability of the results may be compromised.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Although, improvement was greater in the combined KT and CSE group, showing that modalities such as KT and CSE are effective in the treatment of NSCLBP. Additionally, a study by Hernandez-Lucas et al (2023) evaluating the effects of the Back School on non-specific neck pain in adults aged ≥18, showed a beneficial effect on kinesiophobia, however, this study did not have a post-intervention follow-up, making it difficult to ascertain its long-term effect. Furthermore, due to the small sample size, generalisability of the results may be compromised.…”
Section: Discussionmentioning
confidence: 92%
“…The 17 studies selected were published between the years 2011 to 2023. The 17 selected studies (Nassif et al, 2011 ; Miyamoto et al, 2013 , 2018 ; Da Luz Junior et al, 2014 ; Vincent et al, 2014 ; Cruz-Díaz et al, 2017 , 2018 ; Keane, 2017 ; Zadro et al, 2019 ; Galan-Martin et al, 2020 ; Tagliaferri et al, 2020 ; Akodu et al, 2021 ; Vicente-Campos et al, 2021 ; Martins de Sousa et al, 2022 ; Cana-Pino et al, 2023 ; Hernandez-Lucas et al, 2023 ; Ogunniran et al, 2023 ) involved 1,354 participants. Variation in chronic non-specific spine-related pain, exercise/physical activity and measures used to assess kinesiophobia contributed to the significant level of heterogeneity between the studies and reported effect estimates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations